Effects of rolling deformation on microstructure and hardness of Ti-45Al-9Nb-0.3Y alloy - 张树志 张长江 侯赵平 孔凡涛 陈玉勇 (Journal of rare earths, 2016)
The microstructure evolution of as-rolled Ti-45Al-9Nb-0.3Y alloy as well as the nanohardness of β/B2 matrix was investigated by means of scanning electron microscopy（SEM） in backscattered electron mode（BSE） mode, transmission electron microscopy（TEM） and nanoindentation. This high Nb containing Ti Al based alloy was rolled with 50%, 60%, 65% reduction, respectively. Omega phase precipitated in B2 phase with an orientation relationship of {110}_β//{11 2 0}_ω and 〈11 1〉_β//〈0001〉_ω. Moreover, with the increase of deformation reduction, rod-like structure which was formed in γ grain transformed from（α_2＋γ） lamellae structure into α_2 phase only. Additionally, nanoinentation experiment revealed that the precipitation hardening of ω phase increased the hardness of β/B2 phase.